A Summary of the Prostate Cancer Prevention Trials With a Focus on the Role of Vitamin E. (February 2013) - Abu-Shahin, Fadi; Stone, William; Ramsauer, Victoria; Krishnan, Koyamangalath
Prostate cancer is the most common noncutaneous malignancy in men. It is an excellent target for primary prevention. Vitamin E trials conducted for prevention of prostate cancer have had conflicting results with a lower incidence of prostate cancer in the ATBC trial and a higher incidence in the vitamin E arm of the SELECT trial. Most of the clinical trials with vitamin E have been limited to the alpha-tocopherol isoform alone. An increasing body of evidence suggests, however, that the gamma- and delta-isoforms of tocopherol and tocotrienols are more promising with regard to cancer prevention. This review tries to justify our assertion that the gamma- and delta-isoforms of tocopherol and tocotrienol might be superior as prostate cancer preventers.